Amplitude de movimento e dor lombar durante a execução do agachamento livre em mulheres praticantes de musculação - LIMA, Anderson Muller Souza da silva de (2022)
This study aimed to analyze the relationship between the range of motion of the hip and knee and the prevalence of nonspecific low back pain in women who practice resistance training. Forty-one weight-training women with a minimum of 1 year of practice were evaluated, with a weekly training frequency of at least 3 times a week, with a mean age of 30 ± 7.4 years. Active goniometry was used to assess joint range of motion and the pain analog scale (VAS) was used to assess the prevalence and intensity of low back pain while performing the free squat exercise. Statistical analysis was performed using the BioEstat 5.0 software, adopting a significance level of p < 0.05. In the analysis of the prevalence of pain, a percentage of 41.5% was found for those who did not report pain and 58.5% for those who did, indicating a high prevalence of low back pain during the free squat exercise. For pain intensity, we found such percentages of 73.2% who reported mild pain and 26.8% for moderate pain, indicating a high percentage rate of those who feel low back pain during the free squat exercise. In addition, a significant inverse correlation p < 0.03 was found between age and pain intensity, indicating that the older the age, the lower the pain intensity presented in the free squat exercise. As for the prevalence of pain and practice time, a significant direct correlation was found p < 0.04, indicating the longer the practice time, the greater the prevalence of low back pain during the execution of the free squat exercise.